EVERYDAY RELIGION: TAWARAN METODE PENELITIAN SOSIAL BAGI PENGEMBANGAN STUDI ISLAM - Karman Karman (Pascasarjana IAIN Ambon, 2022)
Religion in contemporary sociological studies does not only talk about official discourse, but also everyday lived. This paper describes